Kontribusi Koordinasi Mata Tangan, Kelentukan Pergelangan Tangan dan Keseimbangan Terhadap Kemampuan Untuk Servis Panjang dalam Permainan Bulutangkis Pada Siswa - Herman, Herman (UNIVERSITAS NEGERI MAKASSSAR, 2019)
This study aims to determine the contribution of hand-eye coordination with long serviceability, the contribution of wrist flexion with long serviceability, contribution of balance with serviceability and contribution of hand-eye coordination, wrist flexion and balance to long service in badminton play in MAN 2 Kota students Makassar. The research method or method used in this study is a